ТАЪЛИМ ЖАРАЁНИДА ЎҚИТУВЧИ УСЛУБИНИНГ МОТИВАЦИЯЛОВЧИ ТАЪСИРИ - Тураева, Д.Р. (SCIENCE and SOCIETY, 2024)
This article examines the teacher’s style of activity that influences students’ learning motivation and the individual psychological characteristics of teachers corresponding to the style. A psychological analysis is presented the results of an experiment conducted in this area.
Keywords: teacher; style; teacher’s style of activity; management style; effective style of activity; adaptive style of activity; style of social activity; personal